Strategi Promosi dan Komunikasi Jasa Pendidikan - Mawally Nafis Badri, Muhammad Shofwan; Mu'in, Abdul; Zohriah, Aniz (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Promotion and communication are the keys to the success of marketing, including educational services marketing. Marketing communication is an integral part of communication and is also an integral part of marketing. To discuss this, a literature review method is used, and data is collected through online sources, including books and articles in scholarly journals. Meanwhile, for analysis, content analysis is employed as a technique. The result is that marketing communication in educational services is a two-way exchange of information between the parties involved in marketing activities within the school with the goal of enhancing the customers' perception of the educational product. To ensure its sustainability, educational institutions must be more creative in packaging promotions or educational service communication tailored to the challenges of the current era.